Start-ups' business model changes during the COVID-19 pandemic: Counteracting adversities and pursuing opportunities. (March 2022) - Guckenbiehl, Peter; Corral de Zubielqui, Graciela
This article investigates how start-ups have been affected by, and have responded to, the COVID-19 pandemic by analysing interview data from 32 Australian start-ups during Australia's second wave of COVID-19. A framework and visualisation were developed, capturing unexplored heterogeneity within these start-ups, depending whether the emphasis was upon opportunities or adversity, and the type and extent of business model changes. Six start-up types were identified: stable beneficiaries, business-as-usual continuers, digital adjusters, adversity survivors, opportunity graspers and lemonade makers. The findings suggest that most start-ups responded to the crisis through business model changes because of crisis-induced opportunities and crisis-induced adversity The anaysis found that the interplay between firm size and crisis influences whether start-ups focus on business model adaptation or business model innovation or a combination of both We thus contribute to the literature on business models, crisis management and a newly emerging field focusing on the implications of the COVID-19 pandemic for start-ups.